Multispectral imaging: an effective tool to estimate gar-lic productivity and sanitary aspects - Caligiore Gei, Pablo Fernando (Sociedad Argentina de Informática, 2022)
Garlic is a relevant crop worldwide, with more than 1.6 M hectares and a production of 30 M tons. In Argentina the crop is located in the western part of the country, in the provinces of Mendoza and San Juan. The vast majority of the local production is ex-ported, generating an average income of 150 M USD.